Ludwig von Mises and Libertarian Organisations:: Strategic Lessons - Hülsmann, Jörg Guido (2016)
The author presents the history of Ludwig von Mises’s participation in organizations devoted to liberty, since his defense of free trade in the 1920’s until his participation in the foundation of Mont Pèlerin Society in 1947. Hence, the author illustrates the central role played by Mises in the development of the liberal/libertarian thought in the 20th century.